Workplace discrimination: sexual harassment - Alhabshi, Sharifah Alia; Hassan, Arif (Management Centre, IIUM, 2012)
The case provides a valid example of the challenges faced by a transgender in the workplace, particularly in relation to prejudice, discrimination and sexual harassment. The setting is in an international financial institution in Malaysia that has an inclusive workplace environment where the values and culture of social diversity are embraced by the organization. The case presents the struggle of a Malay male transgender who worked as a sales personnel for the subsidiary company of the organization. A fellow colleague at the workplace harassed him and he was left to defend himself. Although the workplace environment was an inclusive one, the available policy and procedures to handle harassment cases were inadequate to ensure that any harassment complaint is handled in a just and fair manner.